Advanced programmer's guide to SuperVGAs - Sutty, George J. (Brady, 1990)
Offers a graphics programming utility with drawing routines for 256, sixteen, and four color graphics. The text is designed to enable users to utilize fully the many advanced features of the SuperVGAs.